Optical characterization of weakly absorbing PP, PE, and PP/PE films - Boydag, FS; Mamedov, SV; Alekperov, VA; Özcanli, YL (OPTICAL SOC AMER, 2003)
The transmittance, absorbance, and reflectance of polypropylene (PP), polyethylene (PE), and polypropylene/polyethylene (PP/PE) blends prepared by a hot pressing method are investigated. IR and UV spectra of PP, PE, and PP/PE blends (0-80%) in the wavelength range of 200-25000 nm were examined. The optical absorption spectra are presented and the determined values of energy gaps are listed. The results indicate that both direct and indirect transitions may exist. The analyses of the absorption peaks corresponding to oxygen groups for the PP/PE composite (80/20) show low optical density and, therefore, highly different optical behavior than for pure PP. The PP/PE composite is very promising with regard to optical stability. (C) 2003 MAIK Nauka/Interperiodica.
Keywords: POLYMER; Optics; Spectroscopy